Ali Baba and the forty thieves - Daynes, Katie; Mounter, Paddy Kelly, Alison (Usborne London, 2007)
A classic folktale retold with easy-reading text for children who have just started reading alone. Ali Baba has discovered a cave full of treasure. It's a dream come true! But soon he has a nosy brother and forty thieves to deal with..